Shift In Pre-Trial Procedural Law: A Study Using Paradigm Theory - Nuryanta, Muhammad Arif; Hartiwiningsih, Hartiwiningsih; Suwadi, Pujiyono; Frimanda, Nilam (International Conference on Law, Technology, Spirituality and Society (ICOLESS); Vol 5 (2025): The 8th International Conference on Law, Technology, Spirituality and Society (ICOLESS), 2025)
This study seeks to delineate the presence of pre-trial procedures within the Indonesian criminal justice system. This paper aims to examine the existing practice of implementing pre-trial procedures, which reportedly use a quasi-civil procedural law framework. This study employs normative research, utilising both a conceptual and a case approach. The study’s findings indicate that the evolution of Criminal Procedure Law, viewed through the lens of Legal History, has transitioned from the inquisitorial to the accusatory legal concept.  The accusatory concept of law exists only in part.  Consequently, in the execution of pre-trial power, the lack of procedural law necessitates a methodical interpretation that directs attention to Civil Procedure Law.  Consequently, the examination procedure in the execution of pre-trial authority entails the pursuit of formal truth. The Criminal Procedure Code fundamentally aims to ascertain material truth. Consequently, despite the diverse rulings from pre-trial judges, the pre-trial examination process invariably focuses on post-factum evidence, disregarding all subjective actions that fall outside Article 77 of the Criminal Procedure Code in conjunction with Constitutional Court Decision Number 21/PUU-XII/2014 dated 28 April 2015. Decision of the Constitutional Court Number 21/PUU-XII/2014, dated 28 April 2015. b. The legal reform of the Criminal Code has been in progress since the establishment of the Constitutional Court, which serves as a constitutional guardian with the power to evaluate laws in relation to the 1945 Constitution. The series of rulings from the Constitutional Court, particularly Constitutional Court Decision No. 21/2014 as a pivotal ruling, has introduced new dimensions in the discourse surrounding the Criminal Procedure Code, necessitating various conditions for its validity as a procedural legal instrument. The paradigm change in the analysis of the Criminal Procedure Code, particularly regarding pre-trial procedures, is (1). The directive to implement the due process of the model concept; (2). Transgressing the Precautionary Principle, resulting in the infringement of human rights; (3). Subjective activities are subject to testing; and (4).  The optimal and accurate legal procedure signifies a transition in viewpoint from the pursuit of formal truth to the pursuit of material truth.